"No Excuses" Charter Schools: A Meta-Analysis of the Experimental Evidence on Student Achievement. Issue 2 (3rd April 2017) - Cheng, Albert; Hitt, Collin; Kisida, Brian; Mills, Jonathan N.
ABSTRACT: Many most well-known charter schools in the United States use a "No Excuses" approach. We conduct the first meta-analysis of the achievement impacts of No Excuses charter schools, focusing on experimental, lottery-based studies. We estimate that No Excuses charter schools increase student math and literacy achievement by 0.25 and 0.17, respectively, for approximately each year of attendance. These are large and meaningful gains. Moreover, these effects are substantially larger than those of attending other kinds of charter schools. We discuss policy implications and offer necessary caveats.